KONVERGENSI AKUNTANSI DAN RELEVANSI NILAI INFORMASI AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Khairani, Khairani (Imara: JURNAL RISET EKONOMI ISLAM, 2019)
This study aims to explore the value relevance of accounting information in the period before an after the implemented of IFRS in Indonesia uses the price models. Implementation of IFRS was predicted will be increase of value relevance of accounting information. This study uses the value of accounting earnings and book value of equity as a proxy for the value relevance of accounting information. The value relevance of accounting information in the decision-making of investors as reflected in the stock price. The population of this research is a listed public company on the Indonesia Stock Exchange in the period 2009-2015. The data are choice using purposive sampling method, with the result that total sample are 45 companies.  This research analyzed using Linier Regretion, Paired-Sample T Test and significance simultant test. Results of this study indicate that the adoption of IFRS -based standards in Indonesia has been able to improve the value relevance of accounting information.